Algebra for college students - Dugopolski, Mark (New York : McGraw-Hill, 2012)
Part of the "Dugopolski" series, this book provides students and faculty with short explanations of Algebra terms and concepts written in understandable language that is mathematically accurate.
Chapter 1: The Real Numbers -- 1.1 Sets -- 1.2 The Real Numbers -- 1.3 Operations on the Set of Real Numbers -- 1.4 Evaluating Expressions and the Order of Operations -- 1.5 Properties of the Real Numbers -- 1.6 Using the Properties -- Chapter 2: Linear Equations and Inequalities in One Variable2.1 Linear Equations in One Variable2.2 Formulas and Functions -- 2.3 Applications -- 2.4 Inequalities -- 2.5 Compound Inequalities -- 2.6 Absolute Value Equations and Inequalities -- Chapter 3: Linear Equations and Inequalities in Two Variables -- 3.1 Graphing Lines in the Coordinate Plane -- 3.2 Slope of a Line -- 3.3 Three Forms for the Equation of a Line -- 3.4 Linear Inequalities and Their Graphs -- 3.5 Functions and Relations -- Chapter 4: Systems o -- f Linear Equations4.1 Solving Systems by Graphing and Substitution -- 4.2 The Addition Method4.3 Systems of Linear Equations in Three Variables -- 4.4 Solving Linear Systems Using Matrices -- 4.5 Determinants and Cramer$1 (Bs Rule -- 4.6 Linear Programming -- Chapter 5: Exponents and Polynomials -- 5.1 Integral Exponents and Scientific Notation -- 5.2 The Power Rules5.3 Polynomials and Polynomial Functions -- 5.4 Multiplying Binomials -- 5.5 Factoring Polynomials -- 5.6 Factoring ax + bx + c -- 5.7 Factoring Strategy -- 5.8 Solving Equations by Factoring -- Chapter 6: Rational Expressions and Functions -- 6.1 Properties of Rational Expressions and Functions -- 6.2 Multiplication and Division -- 6.3 Addition and Subtraction -- 6.4 Complex Fractions -- 6.5 Division of Polynomials -- 6.6 Solving Equations Involving Rational Expressions -- 6.7 Applications -- Chapter 7: Radicals and Rational Exponents -- 7.1 Radicals -- 7.2 Rational Exponents -- 7.3 Adding, Subtracting, and Multiplying Radicals -- 7.4 Quotients, Powers, and Rationalizing Denominators -- 7.5 Solving Equations with Radicals and Exponents7.6 Complex Numbers -- Chapter 8: Quadratic Equations, Functions, and Inequalities -- 8.1 Factoring and Completing the Square -- 8.2 The Quadratic Formula -- 8.3 More on Quadratic Equations -- 8.4 Quadratic Functions and Their Graphs -- 8.5 Quadratic Inequalities -- Chapter 9: Additional Function Topics -- 9.1 Graphs of Functions and Relations -- 9.2 Transformations of Graphs -- 9.3 Combining Functions -- 9.4 Inverse Functions -- 9.5 Variation -- Chapter 10: Polynomial and Rational Functions -- 10.1 The Factor Theorem -- 10.2 Zeros of a Polynomial Function -- 10.3 The Theory of Equations -- 10.4 Graphs of Polynomial Functions -- 10.5 Graphs of Rational Functions -- Chapter 11: Exponential and Logarithmic Functions -- 11.1 Exponential Functions and Their Applications -- 11.2 Logarithmic Functions and Their Applications -- 11.3 Properties of Logarithms -- 11.4 Solving Equations and Applications -- Chapter 12: Nonlinear Systems and the Conic Sections -- 12.1 Nonlinear Systems of Equations -- 12.2 The Parabola -- 12.3 The Circle -- 12.4 The Ellipse and Hyperbola -- 12.5 Second-Degree Inequalities -- Chapter 13: Sequences and Series -- 13.1 Sequences -- 13.2 Series -- 13.3 Arithmetic Sequences and Series -- 13.4 Geometric Sequences and Series -- 13.5 Binomial Expansions -- Chapter 14: Counting and Probability -- 14.1 Counting and Permutations -- 14.2 Combinations -- 14.3 Probability -- Appendix A Answers to Selected Exercises -- Index.s
Includes index.
Keywords: ALGEBRA